Pembelajaran Berbasis Kearifan Lokal pada Siswa SD di Desa Penglipuran - Raekhan, M. Rino Ryad; Rosna Agustin, Erin; Khoirunnisa, Khoirunnisa; Sinta, Sinta; Mumpuni, Atikah (Jurnal Cahaya Edukasi, 2025)
Abstract : This study aims to explore the implementation of local wisdom-based learning in primary school education in Penglipuran Village. This village is renowned as one of the traditional villages that has preserved its cultural values and traditions, particularly in education. The application of local wisdom-based learning is expected to enhance students' understanding of cultural heritage, strengthen their character, and foster early environmental awareness. This study employs a qualitative research method with a case study approach. Data were collected through observations, interviews, and documentation involving teachers, students, and the local community. The findings indicate that integrating cultural values into the learning process contributes to increased student motivation, deeper understanding of cultural values, and enriched learning experiences. However, challenges remain in its implementation, such as the limited availability of local culture-based learning resources and the lack of training for teachers to effectively adopt this approach. Therefore, collaboration between schools, the government, and the community is essential to develop a more systematic and sustainable local wisdom-based learning model.